Hereditary Breast Cancer in the Brazilian State of Ceará (The CHANCE Cohort): Higher-Than-Expected Prevalence of Recurrent Germline Pathogenic Variants - Gifoni, Ana Carolina Leite Vieira Costa; Gifoni, Markus Andret Cavalcante; Wotroba, Camila Martins; Palmero, Edenir Inez; Costa, Eduardo Leite Vieira; dos Santos, Wellington; Achatz, Maria Isabel (Frontiers in Oncology, 2022)
Purpose There is a significant lack of epidemiological data on hereditary cancer in Northeast Brazil. This is the largest study on the prevalence and mutational spectrum of cancer predisposition genes conducted in this region and the first in the State of Ceará. Methods Patients ≥18 years of age that were referred to CHANCE (Grupo de Câncer Hereditário do Ceará) from March 2014 to December 2020 with testing criteria for breast cancer susceptibility genes according to NCCN v.1.2021 were eligible to participate. The inclusion of patients was limited to one individual per family and to those born in the State of Ceará. All patients underwent a hereditary cancer panel testing with at least 30 genes. Results A total of 355 patients were included, and 97 (27.3%) carried a P/LP germline variant in 18 different genes. Among the 97 P/LP carriers, BRCA1 (31, 31.9%) and BRCA2 (25, 25.7%) were the most frequently mutated genes, followed by PALB2 (10, 10.3%), CHEK2 (7, 7.2%) and ATM (4, 4.1%). A small number of recurrent variants (detected in three or more individuals) in BRCA1, BRCA2, CHEK2 and ATM represented the majority of the P/LP variants described in this cohort. Conclusion In this cohort, the prevalence of L/PL was high, particularly involving the BRCA1, BRCA2, PALB2, CHEK2 and ATM genes and, to a lesser extent than expected, the TP53 gene. A high frequency of recurrent variants was also observed, for which further and larger analyses should clarify the presence of any possible founder effect. Characterizing the mutational profile of cancer predisposition genes in diverse populations may contribute to cancer prevention and therapeutic management.